Prototyping Usability and User Experience: A Simple Technique to Agile Teams - Sousa, Aline de Oliveira; Valentim, Natasha Malveira Costa (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS); 2019: Anais do XVIII Simpósio Brasileiro de Qualidade de Software, 2019)
In the last 15 years, since the Agile Manifesto emerged, many researchers and professionals have attempted to associate agile methodologies with Usability and User Experience (UX). This association happens to create a model that allows for delivering valuable software. However, most of the approaches identified in the literature that combine these concepts demand a lot of knowledge, cost, time, and, resources. Therefore, it is necessary to develop a more accessible technique and help in the cost and the deadline of the project. For this reason, we created a technique that integrates the most popular agile technique, prototyping, with two of the most important software quality criteria, Usability and UX. As a result, the technique called "User Experience and Usability Guideline for Agile Project" (UXUG-AP) has guidelines focusing on Usability and UX characteristics which support the software design. The technique was designed to be used by agile teams, independently of the amount of resources, project size, and the agile methodology adopted.